2019
DOI: 10.15171/jlms.2019.26
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Photobiomodulation Therapy and Bone Marrow Stromal Stem Cells Conditioned Media on Pheochromocytoma Cell Line 12 Against Oxidative Stress Induced by Hydrogen Peroxide

Abstract: Introduction: Bone marrow stromal stem cells (BMSCs), a type of adult stem cells, secrete bioactive molecules such as trophic factors, growth factors, chemokine and cytokines that may be effective against oxidative stress in neurodegenerative diseases. In this study, we examined the protective effect of BMSCs conditioned media (CM) and photobiomodulation therapy (PBMT) on PC12 cells exposed to H2O2 as an oxidative injury model. Methods: BMSCs were cultured and confirmed by flow cytometry analysis and underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…There are a variety of antioxidant systems in cells, while the synergistic antioxidant effect is mainly achieved by eliminating intracellular ROS to prevent oxidative damage to the body [5]. In fact, oxidant/antioxidant levels are critical for neurodegeneration or neuroprotection, in which enzymes such as superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-Px) constitute the key antioxidant defenses [6]. Excessive ROS not only is closely related to mitochondrial dysfunction but also can increase intracellular Ca 2+ concentration and activate some intracellular apoptotic pathways.…”
Section: Introductionmentioning
confidence: 99%
“…There are a variety of antioxidant systems in cells, while the synergistic antioxidant effect is mainly achieved by eliminating intracellular ROS to prevent oxidative damage to the body [5]. In fact, oxidant/antioxidant levels are critical for neurodegeneration or neuroprotection, in which enzymes such as superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-Px) constitute the key antioxidant defenses [6]. Excessive ROS not only is closely related to mitochondrial dysfunction but also can increase intracellular Ca 2+ concentration and activate some intracellular apoptotic pathways.…”
Section: Introductionmentioning
confidence: 99%
“…20 The results of this study showed that PHT can increase the induction of autophagy in the ADSC and also cause the formation of more lipid droplets, which was consistent with the results of other studies. 21…”
Section: Discussionmentioning
confidence: 99%
“…Then, qRT-PCR reactions were performed for three biological replicates on the real-time PCR system (Applied Biosystems StepOne instrument) using SYBR Green Master Mix and sets of primers (Table 1 ). The final analyses were performed using the comparative CT method (2 −ΔΔct ) [ 13 , 34 ].…”
Section: Methodsmentioning
confidence: 99%